2016
DOI: 10.1186/s12879-016-1953-9
|View full text |Cite
|
Sign up to set email alerts
|

Title: role of matrix metalloproteinase −9 in progression of tuberculous meningitis: a pilot study in patients at different stages of the disease

Abstract: BackgroundTBM (Tuberculous meningitis) is severe form of tuberculosis causing death of one third of the affected individuals or leaving two-third of the survivors disabled. MMP-9 (Matrix metalloproteinase-9) is produced by the central nervous system in a variety of inflammatory conditions and has a role in the breakdown of extracellular matrix and blood–brain barrier.MethodsIn this study, the levels of MMP-9 and its inhibitor, TIMP-1 (tissue inhibitor of metalloproteinases-1), were screened using zymography an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…The involvement of these MMPs in granulomatous tissues had been shown separately in different models including mice (Ramos-Martinez et al, 2015 ; Ordonez et al, 2016 ), rabbits (Kubler et al, 2015 , 2016 ), fish (van der Sar et al, 2009 ; Volkman et al, 2010 ), and human tissues (Ong et al, 2015 ; Sathyamoorthy et al, 2015 ). Similar to our results, it has been shown that in human lung tissue biopsies of patients with TB, MMPs can be located in the macrophages surrounding the areas with caseous necrosis, (Elkington et al, 2005 ), at sites of tissue destruction (Green et al, 2010 ) and in cerebrospinal fluid during TB meningitis (Majeed et al, 2016 ). MMP9 is induced in epithelial cells surrounding growing granuloma, but its activity is dependent on the presence of macrophages (Elkington et al, 2007 ; Volkman et al, 2010 ).…”
Section: Discussionsupporting
confidence: 90%
“…The involvement of these MMPs in granulomatous tissues had been shown separately in different models including mice (Ramos-Martinez et al, 2015 ; Ordonez et al, 2016 ), rabbits (Kubler et al, 2015 , 2016 ), fish (van der Sar et al, 2009 ; Volkman et al, 2010 ), and human tissues (Ong et al, 2015 ; Sathyamoorthy et al, 2015 ). Similar to our results, it has been shown that in human lung tissue biopsies of patients with TB, MMPs can be located in the macrophages surrounding the areas with caseous necrosis, (Elkington et al, 2005 ), at sites of tissue destruction (Green et al, 2010 ) and in cerebrospinal fluid during TB meningitis (Majeed et al, 2016 ). MMP9 is induced in epithelial cells surrounding growing granuloma, but its activity is dependent on the presence of macrophages (Elkington et al, 2007 ; Volkman et al, 2010 ).…”
Section: Discussionsupporting
confidence: 90%
“…Tuberculous meningitis (TBM), which arises rarely as an extrapulmonary form of tuberculosis, is associated with neurofunctional complications [146]. In patients with TBM, levels of MMP-2 and MMP-9 were found to be elevated, and high levels of MMP-9 were associated with late neurofunctional deficits [147,148]. Adjuvant dexamethasone during TBM was shown to reduce MMP-9 levels early in treatment and might represent one way by which dexamethasone reduces mortality in TBM [149,150].…”
Section: Metalloproteinases In the Pathogenesis Of Bacterial Meningitismentioning
confidence: 99%
“…MMPs are a family of zinc-dependent endopeptidases with more than 20 different members [28,29]. MMP-9, a member of the MMP family, plays a crucial role in regulating angiogenesis and BM degradation under hypoxic conditions [30,31].…”
Section: Introductionmentioning
confidence: 99%